148 Luma is not essential for cardiac development and function in mice. (June 2018) - Stroud, Matt; Fang, Xi; Zhang, J; Camboa, N; Dalton, ND; Gu, Y; Peterson, KL; Gerace, Larry; Evans, Sylvia; Bradford, W; Chen, Ju
Abstract : Luma is a recently discovered, evolutionarily conserved protein expressed in mammalian heart that is associated with the LInker of Nucleoskeleton and Cytoskeleton (LINC) complex. The LINC complex structurally integrates the nucleus and the cytoplasm, and plays a critical role in mechanotransduction across the nuclear envelope. Mutations in several LINC components in both humans and mice result in various cardiomyopathies, implying they play essential, non-redundant roles. A single amino acid substitution of serine 358 to leucine (S358L) in Luma is the unequivocal cause of a distinct form of arrhythmogenic cardiomyopathy. However, the role of Luma in heart has remained obscure. In addition, it also remains to be determined how the S358L mutation in Luma leads to cardiomyopathy. To determine the role of Luma in the heart, we first determined the expression pattern of Luma in mouse heart. Luma was sporadically expressed in cardiomyocytes throughout the heart, but was highly and uniformly expressed in cardiac fibroblasts, and vascular smooth muscle cells. We also generated germline null Luma mice and discovered that germline null mutants were viable and exhibited normal cardiac function. Luma null mice also responded normally to pressure overload induced by transverse aortic constriction. In addition, localization and expression of other LINC complex components in both cardiac myocytes and fibroblasts was unaffected by global loss of Luma. Furthermore, we also generated and characterised Luma S358L knock-in (KI) mice, which displayed normal cardiac function and morphology. Our data suggest that Luma is dispensable for murine cardiac development and function and that the Luma S358L mutation alone may not cause cardiomyopathy in mice.